Carbonic anhydrase subunits of the mitochondrial NADH dehydrogenase complex (complex I) in plants - Braun, Hans Peter (2007)
The mitochondrial NADH dehydrogenase complex (complex I) of plants has a molecular mass of about 1000 kDa and is composed of more than 40 distinct protein subunits. About three quarter of these subunits are homologous to complex I subunits of heterotrophic eukaryotes, whereas the remaining subunits are unique to plants. Among them are three to five structurally-related proteins which resemble an archaebacterial g-type carbonic anhydrase (gCA). The gCA subunits are attached to the membrane arm of complex I on the matrix-exposed side and form an extra spherical domain. At the same time, they span the inner mitochondrial membrane and are essential for assembly of the protein complex. Expression of the genes encoding gCA subunits is reduced if plants are cultivated in the presence of elevated CO2 concentrations. The functional role of these subunits within plant mitochondria is currently unknown but might be related to photorespiration. We propose that the complex I-integrated gCAs are involved in mitochondrial HCO3ˉ formation to allow efficient recycling of Ci for CO2 fixation in chloroplasts under high light conditions.